Adherence to a healthy lifestyle and the risk of type 2 diabetes in Chinese adults - Lv, J; Yu, C; Guo, Y; Bian, Z; Yang, L; Chen, Y; Hu, X; Hou, W; Chen, J; Chen, Z; Qi, L; Li, L; et al. (Oxford University Press, 2017)
Background: Simultaneously adhering to multiple healthy lifestyle factors has been related to up to 90% reduction in type 2 diabetes (T2DM) incidence in White populations; however, little is known about whether such protective effects persist in other non-White populations. Methods: We examined the associations of six lifestyle factors with T2DM in the China Kadoorie Biobank of 461 211 participants aged 30-79 years without diabetes, cardiovascular diseases or cancer at baseline. We defined low-risk lifestyle factors as non-smoking or having stopped for reasons other than illness; alcohol consumption of <30 g/day; upper quarter of the physical activity level; diet rich in vegetables and fruits, low in red meat and with some degree of replacement of rice with wheat; body mass index (BMI) of 18.5-23.9 kg/m 2 ; and waist-to-hip ratio (WHR) <0.90 (men)/<0.85 (women). Results: During a median of 7.2 years of follow-up, we identified 8784 incident T2DM. In multivariable-adjusted analyses, two important risk factors for developing T2DM were higher BMI and WHR. Compared with participants without any low-risk factors, the hazard ratio [95% confidence interval (CI)] for those with at least three low-risk factors was 0.20 (0.19, 0.22). Approximately 72.6% (64.2%, 79.3%) of the incident diabetes were attributable to the combination of BMI, WHR, diet and physical activity. The population attributable risk percentage (PAR%) of diabetes appeared to be similar for men and women, and higher among urban, older and obese participants. Conclusions: Our findings indicate that adherence to a healthy lifestyle may substantially lower the burden of T2DM in the Chinese population.